Anti-Neurotoxins from Micrurus mipartitus in the Development of Coral Snake Antivenoms (2022)
ABSTRACT: In Colombia, the genus Micrurus includes 30 species, of which M. mipartitus and M. dumerilii are the most widely distributed. Micrurus causes less than 3% of the approximately 5000 cases of snakebite per year. The elapid envenomation caused by the snakes from the Micrurus genus, are characterized by the severity of their clinical manifestations, due to the venom neurotoxic components such as three-finger toxins (3FTx) and phospholipases (PLA2). The treatment for snakebites is the administration of specific antivenoms, however, some of them have limitations in their neutralizing ability. A strategy proposed to improve antivenoms is to produce antibodies against the main components of the venom. The aim of this work was to produce an antivenom, using an immunization protocol including the main 3FTx and PLA2 responsible for M. mipartitus lethality. The antibody titers were determined by ELISA in rabbits’ serum. The immunized animals elicited a response against toxins and whole venom. The Immunoglobulin G (IgGs) obtained were able to neutralize the lethal effect of their homologous toxins. A combination of antivenom from M. mipartitus with antitoxins improved their neutralizing ability. In the same way, a mixture of anti 3FTx and PLA2 protected the mice from a 1.5 median lethal dose (LD50) of M. mipartitus venom. The results showed that this might be a way to improve antibody titers specificity against the relevant toxins in M. mipartitus venom and indicated that there is a possibility to develop and use recombinant 3FTx and PLA2 toxins as immunogens to produce antivenoms. Additionally, this represents an alternative to reduce the amount of venom used in anti-coral antivenom production.